Bounding Revenue Comparisons across Multi-Unit Auction Formats under ε-Best Response - Chapman, James T. E; McAdams, David; Paarsch, Harry J (American Economic Review, 2007)
Bounding Revenue Comparisons across Multi-Unit Auction Formats under ε-Best Response by James T. E. Chapman, David McAdams and Harry J. Paarsch. Published in volume 97, issue 2, pages 455-458 of American Economic Review, May 2007